Increasing Reading Comprehension through the Use of Kaili Folktales - Dewi Laras; Jamiluddin Jamiluddin; Desrin Lebagi; Mukrim Mukrim (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
The research employed Kaili folktales to increase reading comprehension of the ninth grade students at SMP Negeri 20 Palu. The primary research question is whether incorporating Kaili folktales through this environment my increase students’ reading comprehension. The research used a pre-experimental design in a quantitative approach that included a pre-test, treatment, and post-test. The research population was the 87 ninth grade students of SMP Negeri 20 Palu, with 29 students as sample from class IX B selected through purposive sampling. The research instrument was a reading comprehension test that was given as a pre-test and post-test. Data analysis was conducted using SPSS 22. The results showed that using Kaili folktales increased students’ reading comprehension significantly, as evidenced by a higher mean score in the post-test compared to the pre-test (61.972>34.221). The p-value determined of 0.00, which is lower than the alpha value of 0.05, supported the conclusion that applying of Kaili folktales increased students’ reading comprehension statistical significantly. As a result, the researcher concluded that Kaili folktales might effectively increase students’ reading comprehension of the ninth grade at SMP Negeri 20 Palu